A nationwide study of why and how acute adolescent psychiatric units use restraint. (30th March 2016) - Furre, Astrid; Sandvik, Leiv; Friis, Svein; Knutzen, Maria; Hanssen-Bauer, Ketil
Abstract: The purpose of this study was to examine the type, reason, and duration of restraint episodes in acute adolescent psychiatric units. In a retrospective design we included data from paper-based protocols on all episodes of restraint and data from electronic patient records during 2008–2010 in all acute adolescent psychiatric in-patient units in Norway ( N =16). The episodes of restraint included mechanical and pharmacological restraint, seclusion and physical holding that was not part of the implementation of forced feeding. Six-and-a-half per cent of all 4099 adolescents admitted to the acute units experienced restraint. Of the 2277 episodes, 13.4% were mechanical restraint, 1.6% were pharmacological restraint, 5.9% were seclusion and 78.7% were physical holding. The median number of restraint episodes per patient was two, the range was 1–171 and 47 patients (18%) experienced ≥10 episodes. The most common reason for using restraint was harming others. The median duration of the mechanical restraint episodes was 3.5 h. The median duration of seclusion was 30 min and the median duration of physical holding was 10 min. Highlights: We examine restraint use in all the Norwegian acute adolescent psychiatric units. Physical holding was the most frequent type of restraint used. Physical holding had a median duration of 10 min. Harming others was the most common reason for the use of restraint.